Caregiver burden among parents of school-age children with asthma: a cross-sectional study - Fang Yang; Jingru Zhou; Hongying Xiao; Xia Wu; Yingjuan Cui; Houqiang Huang; Silin Zheng; Huawei Li (Frontiers in Public Health, 2024)
ObjectiveTo investigate the caregiver burden of parents of school-age children with asthma and analyze the factors influencing their caregiver burden.MethodsA convenience sampling method was used to select 366 parents of school-age children with asthma who visited the outpatient departments of three tertiary hospitals in Sichuan Province, China, from January 2021 to July 2021. A general information questionnaire and the Caregiver Burden Inventory (CBI) were used to assess the current caregiver burden and analyze the influencing factors.ResultsThe caregiver burden score of parents of school-age children with asthma was 27 (17, 39), with 40.43% of parents experiencing moderate to high levels of burden. Detailed results of univariate analysis showed that there were significant differences in caregiver burden scores based on parents’ gender, highest education level, number of children, occupation, family history of asthma, monthly family income, annual medical expenses for the child, child’s gender, whether the child had undergone lung function tests, number of emergency visits due to asthma exacerbation in the past 3 months, and whether the child had missed school due to asthma exacerbation in the past 3 months (p < 0.1). Detailed results of multivariate analysis showed that parents’ gender, occupation, family history of asthma, monthly family income, annual medical expenses for the child, number of emergency visits due to asthma exacerbation in the past 3 months, and whether the child had missed school due to asthma exacerbation in the past 3 months were independent risk factors for caregiver burden in parents of school-age children with asthma (p < 0.05).ConclusionParents of school-age children with asthma experience a certain level of caregiver burden, with over one-third of parents experiencing moderate to high levels of burden. Being a mother, being a worker, having no family history of asthma, having low monthly family income, having high annual medical expenses for the child, having frequent emergency visits due to asthma exacerbation in the past 3 months, and having missed school due to asthma exacerbation in the past 3 months are independent risk factors for caregiver burden in parents of school-age children with asthma, healthcare providers should develop feasible coping strategies, such as paying attention to caregivers’ psychological condition to reduce the burden of caring for parents of school-age children with asthma. The entire society should also make efforts in improving social support and strengthening healthcare coverage in order to achieve the aforementioned goals.